PERBANDINGAN AKTIVITAS ANTIBAKTERI ANTARA Lactobacillus casei subsp. casei R-68 DAN Lactobacillus casei KOMERSIL TERHADAP Staphylococcus aureus FNCC-15 DAN Escherichia coli FNCC-19 - Fitri ' Khairunnisa; Usman ' Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of the study was to compare the antibacterial activity of Lactobacillus casei subsp. casei R-68 and Lactobacillus casei commercial against Staphylococcus aureus FNCC-15 and Escherichia coli FNCC-19. The research was carried out experimentally by testing isolates of Lactobacillus casei subsp. casei R-68 and Lactobacillus casei commercial in a petri dish that already contains pathogenic bacteria. Antibacterial activity was tested using the well diffusion method, the data obtained were analyzed descriptively. The results showed that Lactobacillus casei subsp. casei R-68 has the ability to inhibit pathogenic bacteria by inhibition smaller than Lactobacillus casei commercial. The average inhibition zone diameter of lactic acid bacteria isolates against Staphylococcus aureus FNCC-15 ranged from 7.40 to 8.10 mm and Escherichia coli ranged from 9.80 to 10.23 mm. Keywords : Antimicrobials, Lactic acid, Lactobacillus casei subsp. casei R-68, Lactobacillus casei commercial.